The role of psychological climate in outstanding performance - an exploratory and analytical research in a sample of colleges at the University of Karbala - Muayid Al-Saedy; Yazan Salem Mohammed (Iraqi Journal for Administrative Sciences, 2025)
The research cared with diagnosis the role of climate psychological variable dimensions ( ) as a interpretative variable and performance dimensions (Financial perspective, Customer Perspective, Internal process Perspective, Learning & Growth Perspective) as a dependent variable, conducted in a number of colleges of the University of Karbala as selected random sample of employees amounted to strong (250) employees polled by questionnaire prepared for this purpose, used Nonparametric statistical tools test hypotheses, to reach a number of conclusions and recommendations of the task.